The German UMTS Design: Insights From Multi-Object Auction Theory - Christian Ewerhart; Benny Moldovanu (Center for Economic Studies and ifo Institute (CESifo), 2002)
We briefly survey several insights about value and revenue maximization in multi-object auctions and apply them to the German (and Austrian) UMTS auction. In particular, we discuss in detail the exposure problem that caused firms in Germany to pay almost Euro 20 billion for nothing.
Keywords: 330